Living cationic polymerization of vinylnaphthalene derivatives. Issue 22 (2nd September 2013) - Shinke, Yu; Kanazawa, Arihiro; Kanaoka, Shokyoku; Aoshima, Sadahito
ABSTRACT The living cationic polymerization of 6‐tert‐butoxy‐2‐vinylnaphthalene (tBOVN), a vinylnaphthalene derivative with an electron‐donating group, was achieved with a TiCl4/SnCl4 combined initiating system in the presence of ethyl acetate as an added base at –30 °C. The absence of side reactions at low temperature was confirmed by 1H NMR analysis of the resulting polymer. In contrast to this controlled reaction at –30 °C, reactions performed at higher temperature, such as 0 °C, frequently involved unwanted intramolecular or intermolecular Friedel–Crafts reactions of naphthalene rings due to the high electron density of these rings. The cationic polymerization of 6‐acetoxy‐2‐vinylnaphthalene, a derivative with an acetoxy group, was also controlled under similar conditions, but chain transfer reactions were not completely suppressed during the polymerization of 2‐vinylnaphthalene. The glass transition temperature (Tg) of the obtained poly(tBOVN) was 157 °C, a value higher by 94 °C than that of the corresponding styrene derivative. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4828–4834